1994
DOI: 10.1144/gsjgs.151.4.0697
|View full text |Cite
|
Sign up to set email alerts
|

Structural synthesis of S Staffordshire, UK: implications for the Variscan evolution of the Pennine Basin

Abstract: The presence of strata of Westphalian A to possibly Stephanian age in south Staffordshire, located at the southern margin of the Pennine Basin, provides a rare control on the timing of late Carboniferous deformation in Central England. During Westphalian A—C times, sedimentation in south Staffordshire was controlled by thermal subsidence, with a superimposed influence of synsedimentary normal and reverse faulting. Alkaline basic igneous activity occurred during Westphalian C times, synchronous with uplift of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Lavas, sills and small vents of Westphalian A to C age are found along the southern margin of the WalesLondon-Brabant High (Waters et al 1994); sills and lavas are found in the Westphalian C/D sequences of Oxfordshire, and in the earlier Westphalian of Berkshire (Poole 1977;Foster et al 1989). Igneous features are known to have produced a range of associated fault styles, for example radial and ring patterns around vents, including the crypto-volcanic vents interpreted by Barnett (1985).…”
Section: Faults Resulting Solely From Syn-depositional Igneous Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…Lavas, sills and small vents of Westphalian A to C age are found along the southern margin of the WalesLondon-Brabant High (Waters et al 1994); sills and lavas are found in the Westphalian C/D sequences of Oxfordshire, and in the earlier Westphalian of Berkshire (Poole 1977;Foster et al 1989). Igneous features are known to have produced a range of associated fault styles, for example radial and ring patterns around vents, including the crypto-volcanic vents interpreted by Barnett (1985).…”
Section: Faults Resulting Solely From Syn-depositional Igneous Processesmentioning
confidence: 99%
“…In South Staffordshire, Barnsley (1964) identified the "Brinsford Axis", a small positive feature paralleling the local NNW structural trend, across which several Westphalian A and B sequences are attenuated. Waters et al (1994) discussed field relationships between Westphalian sequences and various structures towards the southern basin margin in south Staffordshire, and concluded that extensional and compressional regimes overlapped through much of the Westphalian, with Variscan compression eventually becoming dominant. Some specific active faults were inferred from depositional patterns.…”
Section: The Pennine Basin and Its Sub-basins In Northern England (Wementioning
confidence: 99%
See 2 more Smart Citations
“…By Namurian times the Pennine Basin was dominated by thermally induced subsidence (Leeder 1982;Collinson 1988 1990). By late Carboniferous times the influence of thrusting, to the south of the basin, resulted in flexurally induced subsidence (Leeder 1988: Waters et al 1994Corfield et al 1996).…”
Section: Evolution Of the Pennine Basinmentioning
confidence: 99%